2021
DOI: 10.1111/cen.14598
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary aldosteronism in type 2 diabetes mellitus and hypertension: A prospective study from Western India

Abstract: Objective Type 2 diabetes mellitus (T2DM) and hypertension commonly coexist; however, underlying primary aldosteronism (PA) can lead to worsening of hypertension, glycemia and cardiovascular risk. We aim to screen patients with T2DM and hypertension for PA by conducting a prospective monocentric study from Western India, which included adults with T2DM and hypertension from the outpatient diabetes clinic. Design Prospective study. Patients and Measurements Patients with an aldosterone renin ratio of ≥1.6 ng/dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The results of this study show a prevalence of PA in patients with HDM-2 that is much higher (34.3%) than ever reported, which has ranged from 0.0 to 22.4% [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In addition, an exaggerated aldosterone response to stress through ACTH administration was observed in another 10.3% of the tested HDM-2 non-PA patients.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The results of this study show a prevalence of PA in patients with HDM-2 that is much higher (34.3%) than ever reported, which has ranged from 0.0 to 22.4% [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In addition, an exaggerated aldosterone response to stress through ACTH administration was observed in another 10.3% of the tested HDM-2 non-PA patients.…”
Section: Discussionmentioning
confidence: 49%
“…In the first published study in which only the basal plasma aldosterone concentration/plasma renin activity (PAC/PRA) ratio (>70) was used for the diagnosis of PA, no PA cases were detected among 61 HDM-2 patients [ 18 ]. In other published studies, the PA prevalence in HDM-2 ranged between 4.1% and 22.4% [ 19 , 20 , 21 , 22 , 23 , 24 ]. In these studies, the diagnosis of PA was based on the standard methodology initially using as a screening test the basal PAC/PRA ratio and as confirmatory test mainly the 2 lt saline infusion.…”
Section: Discussionmentioning
confidence: 95%
“…Prevalence studies have reported, 50-55 years as the average age of PH patients at diagnosis[ 15 , 18 ]. The mean age of individuals at presentation was similar in the current study across three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our PH subjects with T2DM had a mean diabetes duration of 6.0 ± 4.7 years compared to mean duration of hypertension of 14.8 ± 7.4 years. A recent study in diabetes subjects reported hypertension predates DM diagnosis in PH patients compared to EH, whereas diabetes diagnosis antedate hypertension detection[ 18 ]. A meta-analysis reported, 15.2% prevalence of new onset T2DM in PH patients, corroborating PH pathophysiology leading to dysglycemia and T2DM[ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[91] Current guidelines do not yet endorse screening for PA in patients with atrial fibrillation. [12,38] Stroke, [92,93] diabetes mellitus, [94,95] and obesity [96] are other disorders associated with overt PA. Further epidemiologic and mechanistic studies are needed to understand these associations prior to expanding PA screening recommendations.…”
Section: Other Conditions Associated With Pamentioning
confidence: 99%